Effect of Surface Microstructures on Hydrophobicity and Barrier Property of Anticorrosive Coatings Prepared by Soft Lithography - Dawei Zhang; Haiyang Li; Xiaoli Chen; Hongchang Qian; Xiaogang Li (Advances in Materials Science and Engineering)
Enhancing the hydrophobicity of organic coatings retards their interaction with water and often leads to better protectiveness over metal corrosion. In this study, a soft lithography method was used to prepare epoxy coatings which showed surface microstructures in high replication to sandpapers. The effect of microstructures on coating’s hydrophobicity and barrier property was investigated. Compared to flat coatings, the microstructured coatings showed much higher water contact angles, which further increased with finer sandpapers. Determined by electrochemical impedance spectroscopy (EIS), the flat coating exhibited a higher anticorrosive performance than the microstructured coatings. With the use of finer sandpaper, the groove size of the corresponding microstructured coating was reduced. And a lower anticorrosive performance was observed since more defects might be formed in a given area of coating during the imprinting process. As the groove size of the coatings was further decreased to 5.7 µm, the microstructures became too small for water to easily penetrate through. Therefore, trapped air acted as an additional barrier and contributed to an increased anticorrosive performance compared to other microstructured coatings.